Environmentally Enhanced Turbines for Hydropower Plants: Current Technology and Future Perspective - Quaranta, Emanuele; Pérez-Díaz, Juan I.; Romero–Gomez, Pedro; Pistocchi, Alberto (Frontiers in Energy Research, 2021)
Environmentally enhanced turbines (EETs) have gained attention in the past two decades in order to reduce environmental impacts of hydropower plants on fish communities and on water quality. In this mini-review the main solutions are discussed in this context, focusing on the Alden and Minimum Gap Runner turbines to reduce fish injury and on self-aerating and self/free-lubricant turbines to improve water quality. The review shows that EETs can be efficiently adopted instead of traditional turbines: EETs are cost-effective, efficient in terms of energy generation and have shown to reduce environmental impacts. Scientific gaps are also highlighted and case studies reported to better support refurbishment projects.